The synthesis of magnesium silicate hydroxide with different morphologies and the comparison of their tribological properties. (March 2018) - Wang, B.; Chang, Q.Y.; Gao, K.; Fang, H.R.; Qing, T.; Zhou, N.N.
Abstract: The tribological properties of magnesium silicate hydroxide (MSH) synthesized at different hydrothermal conditions as lubricant additives were investigated. The morphologies and structures of synthetic MSH were characterized by SEM, TEM, XRD and XRF. The tribological properties of MSH were evaluated using a four-ball friction and wear tester. It is found that different morphologies and structures of MSH are formed through different mechanisms depending on the temperature and reaction-time. Using synthetic MSH as an additive forms a tribofilm on the sliding surface and significantly improve the tribological properties of the oil. MSH with a tubular crystal structure has the best anti-wear property because it is more likely to deposit, adsorb and spread on the friction surface, and thus forms a denser tribofilm. Highlights: MSH are formed through different mechanisms depending on hydrothermal conditions. Temperature and time are the main influencing factors of morphology of MSH. MSH with different structures all can improve the anti-wear property of oil. Tubular MSH has better anti-wear property than lamellar MSH at maximum pressure of 3.91 GPa. Tubular MSH is more readily to form a tribofilm on the worn surfaces than lamellar MSH.